NFE2L1/Nrf1 serves as a potential therapeutical target for neurodegenerative diseases - Kamila Łuczyńska; Zhengwen Zhang; Tadeusz Pietras; Yiguo Zhang; Hiroaki Taniguchi (Redox Biology, 2024)
The failure of the proper protein turnover in the nervous system is mainly linked to a variety of neurodegenerative disorders. Therefore, a better understanding of key protein degradation through the ubiquitin-proteasome system is critical for effective prevention and treatment of those disorders. The proteasome expression is tightly regulated by a CNC (cap'n'collar) family of transcription factors, amongst which the nuclear factor-erythroid 2-like bZIP factor 1 (NFE2L1, also known as Nrf1, with its long isoform TCF11 and short isoform LCR-F1) has been identified as an indispensable regulator of the transcriptional expression of the ubiquitin-proteasome system. However, much less is known about how the pivotal role of NFE2L1/Nrf1, as compared to its homologous NFE2L2 (also called Nrf2), is translated to its physiological and pathophysiological functions in the nervous system insomuch as to yield its proper cytoprotective effects against neurodegenerative diseases. The potential of NFE2L1 to fulfill its unique neuronal function to serve as a novel therapeutic target for neurodegenerative diseases is explored by evaluating the hitherto established preclinical and clinical studies of Alzheimer's and Parkinson's diseases. In this review, we have also showcased a group of currently available activators of NFE2L1, along with an additional putative requirement of this CNC-bZIP factor for healthy longevity based on the experimental evidence obtained from its orthologous SKN1-A in Caenorhabditis elegans.